Hierarchical Linear Modeling of Body Surveillance Frequency: Linking Media Consumption Intensity and Internalized Thin-Ideal in Adolescent Females - Echeverría, Martín; Székely, Ádám; Sigurðardóttir, Arna (Psychology of Woman Journal, 2026)
Objective: The objective of this study was to utilize a multilevel statistical framework to examine how individual-level media consumption intensity and internalized thin-ideal uniquely predict body surveillance frequency, and to determine whether the magnitude of these relationships varies significantly across distinct high school contexts among adolescent females.Methods and Materials: A cross-sectional design was employed, utilizing a sample of N=1348 Hungarian adolescent females nested within multiple high schools. Participants completed a battery of validated self-report psychometric instruments, including a media exposure inventory, the Sociocultural Attitudes Towards Appearance Questionnaire-4 to assess thin-ideal internalization, and the surveillance subscale of the Objectified Body Consciousness Scale. Data were analyzed using Hierarchical Linear Modeling to appropriately partition the variance between individual psychological traits (Level 1) and the overarching sociocultural school contexts (Level 2), while controlling for baseline Body Mass Index.Findings: The calculation of the unconditional null model yielded an Intraclass Correlation Coefficient of 12.8%, confirming that a significant proportion of the variance in body surveillance frequency is attributable to between-school differences. Main effects modeling demonstrated that both intense media consumption and the internalized thin-ideal were robust, significant positive predictors of body surveillance at Level 1. Random slopes analyses revealed that the predictive relationship between the internalized thin-ideal and body surveillance varied significantly across different educational environments; conversely, the random slope for media consumption intensity was not statistically significant, indicating a uniformly detrimental effect across all schools. Additionally, Body Mass Index exhibited a significant positive association with heightened self-surveillance behaviors.Conclusion: Body surveillance among adolescent females is a deeply context-dependent phenomenon where the psychological harm of internalizing societal beauty standards is significantly magnified or buffered by the specific sociocultural climate of the school environment, underscoring the critical need for systemic, whole-school interventions.